Design and Analysis of Impulse Radio (IR) Based UWB Transmitter with Antenna (MIST International Journal of Science and Technology, 2022)
The use of ultra-wideband (UWB) in target detection, radar and wireless connectivity, specifically in the medical world, has attracted a lot of attention. The concept that the IR-UWB system does not necessarily require carrier signals is one of its most appealing features. IR-UWB can transmit information using short Gaussian monocycle pulses. In light of these advantages, this paper proposes a novel UWB transmitter system which consists of UWB signal generating circuits and UWB antenna, which work together to create entire UWB transmitter. It is based on impulses and has a simple architecture with low power consumption. The proposed transmitter is realized in Cadence tools with 90nm CMOS technology and proposed UWB antenna is simulated using Advanced Design System (ADS) simulator software. In addition, the transmitter circuit and the antenna are co-simulated using ADS software. The illustrated UWB transmitter uses a low-power supply and generates 359.44mv pulse amplitude with pulse duration of 100ps for the Gaussian monocycle pulse. Due to its increased output voltage swing and reduced power consumption when comparing to other circuits, the proposed architecture is functional and suitable for use in short-range wireless networks and medical applications.MIJST, Vol. 10, December 2022: 01-09DOI: https://doi.org/10.47981/j.mijst.10(03)2022.337(01-09)